Development of Warehouse Management System to Manage Warehouse Operations - Kusuma Dewi, Irena; Nur Shofa, Rahmi (Journal of Applied Information System and Informatic (JAISI), 2023)
The Warehouse Management System (WMS) is software designed to assist in managing and monitoring warehouse processes. The purpose of this research is to improve warehouse operational management by developing a WMS using the Extreme Programming method and implementing a monitoring system to display real-time temperature and humidity measurements. The research addresses issues observed in the warehouse operations of PT. Shippindo Teknologi Logistik (Shipper), a warehouse rental services company. The problems identified in Shipper's warehouse operations largely stem from human errors. Hence, this research aims to provide a viable solution to reduce human errors by implementing various management processes, including inbound and outbound management and tracking, as well as visualizing product placement within the racks using rack maps. Additionally, the integration of a temperature and humidity monitoring system in the warehouse helps monitor the warehouse's condition in real-time. Testing using the black-box method for WMS in this research was successful, demonstrating that the system can execute all functions and display temperature and humidity data as per the designed specifications (inbound, mapping, storage, temperature and humidity monitoring, outbound). The average error in temperature and humidity measurements is relatively low, with 0.9% for temperature and 1.3% for humidity. However, further development is still required to enhance the system for better performance. This includes creating a more robust model for product detection labeling on the storage page to improve label accuracy and developing control systems for advanced temperature and humidity monitoring.